BEHAVIOR OF REINFORCED SELF-COMPACTING CONCRETE BEAMS CONTAINING STEEL FIBERS AND RECYCLED COARSE AGGREGATES - Mohammed Abd, Lubna (Journal of Engineering and Sustainable Development, 2018)
Concrete wastes are generally delivered to landfill sites for disposal. Due to increased charges of landfills and shortage of natural coarse aggregate (NCA), recycled coarse aggregate (RCA) (resulting from concrete wastes) is growing interest in building engineering. It is sustainable to use recycled construction materials to preserve the natural resources and maintain the environment of cities. In the present study, RCA was used as a full replacement of NCA in some specimens of beams to produce self-compacting concrete (SCC). The experimental work consists of casting and testing eight rectangular simply supported reinforced concrete beams of (1200*180*250) mm for length, width, and height respectively with concentric point load as well as tests for control specimens to determine the mechanical properties of SCC. Four of these eight beams were tested for flexural and the other four beams for shear behavior. The present research includes the following main variables: transverse reinforcement (stirrups spacing, 50 mm and 100 mm), coarse aggregate (RCA and NCA), and steel fibers of (Vf = 0.5%). All beams have constant longitudinal steel reinforcement ratio=0.008. Experimental results have generally shown that ultimate loads (Pu) of beams made with RCA were approximately close to the results of beams made with NCA by percentages (1.08% and 1.11%) for flexural and shear behavior respectively. RCA can be used as a full replacement in the future construction industry. The presence of steel fibers increases the maximum deflection of beams by 1.55% for flexural and 1.02% for shear behavior.